The impact of current-loop control parameters on the electromagnetic transient voltage performance of voltage-source converter - Ding, Xiaoyu; Chen, Hongwei; Zhou, Xiaobo; Shi, Qianhong; Wang, Guanzhong (Frontiers in Energy Research, 2024)
Since the large-scale integration of renewable energy sources into the AC grid has led to a relative decline in the voltage support capacity of the grid and the deterioration of the voltage dynamic at the grid connection point, especially under fast-scale conditions, the voltage disturbance has become more obvious. To improve the dynamic characteristics of the electromagnetic transient voltage at the grid connection point, this paper uses a practical dynamic damping method to analyze the impact of the converter current inner loop, feedforward voltage, and other links on the dynamic performance of the electromagnetic transient voltage. First, the current inner loop dynamic in the converter’s synchronous coordinate is converted into an equivalent transfer function in the stationary coordinate, and the transfer function between the transient voltage disturbance at the grid connection point and the inner loop current output is established. On this basis, the Bode diagram and the vector diagram of the transfer function in the weak damping frequency band are used to analyze the dynamic damping of the current inner loop parameters and voltage feedforward filter parameters on the voltage disturbance at the grid connection point. The results indicate that moderately increasing the current inner loop bandwidth or reducing the feedforward filter bandwidth can help enhance the electromagnetic transient voltage stability of the grid connection point, but increasing the current inner loop bandwidth will worsen the low-frequency damping characteristics and reduce the feedforward filter bandwidth will still help increase low-frequency damping.